Impact of ascorbic acid on the level of anthocyanins and polyphenols in aronia juice during heat treatment - Hamaidia Meriem Serine (Proceedings of the International Symposium on Analytical and Environmental Problems, 2024)
This study examines the effects of 1% ascorbic acid and varying heat treatments (60°C and 80°C) on total anthocyanin content (TAC), total phenolic content (TPC), and antioxidant capacity (FRAP) in Aronia juice. The results show that ascorbic acid and temperature had minimal impact on total anthocyanin content (TAC), with no significant differences observed between the 0% and 1% ascorbic acid treatments at both 60°C and 80°C (p>0.05). Meanwhile the TPC results show that adding 1% ascorbic acid significantly increased total phenolic content (TPC) at both 60°C and 80°C, with the highest values at 10 minutes for 60°C (4142.63±85.77 GAE mg/L) and 30 minutes for 80°C (3660±229.19 GAE mg/L), while 60°C consistently yielded higher TPC than 80°C. Additionally, the antioxidant capacity values indicate that 1% ascorbic acid significantly increased (FRAP) values compared to 0% at both 60°C and 80°C, with the highest value at 60 minutes (12.865.69±527.08 mg/L at 60°C), while (FRAP) values at 80°C were significantly lower than those at 60°C. In conclusion, while ascorbic acid and temperature had minimal effects on total anthocyanin content (TAC), the addition of 1% ascorbic acid significantly boosted total phenolic content (TPC) and antioxidant capacity (FRAP), particularly at 60°C. These findings highlight the potential of ascorbic acid in enhancing the antioxidant properties of Aronia juice during heat treatment.